Frequency domain full-waveform inversion in a fluid-saturated poroelastic medium. Issue 1 (22nd December 2020) - Yang, Qingjie; Malcolm, Alison
SUMMARY: Determining subsurface properties is of fundamental importance in exploration seismic imaging. Poroelasticity theory provides an opportunity to extract quantitative fluid- and attenuation-dependent properties from seismic data. Following Pratt's frequency-domain full-waveform-inversion (FWI) procedure and extending the basic FWI equations from the elastic case to the poroelastic case, we implement poroelastic FWI (PFWI) of fluid-saturated porous media. By analysing the sensitivity kernels of poroelastic parameters, we explain the reason why some parameters are more difficult to recover than others. We also show the analytical and numerical radiation patterns based on which we predict the trade-offs among parameters. In numerical experiments, we invert two models to demonstrate the feasibility and effectiveness of the proposed PFWI and to verify our predictions about trade-offs for two-parameter PFWI. Finally, we discuss the various factors that influence the inversion results.